(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
A study was conducted to elucidate the prescence of T.gondii antibodies in the serum of slaughtered cattle, sheep & goats in Mosul abattoir. The study was carried out during the period from October 2002 to March 2003. For serological tests, 300 serum samples were collected from (100) of each slaughtered cattle, sheep & goats. Serum samples collected from slaughtered goats showed the highest percentage of infection using latex agglutination test and was (54%), followed by sheep (49%), while the lowest percentage (23%) was detected in cattle serum. To determine antibodies in positive serum samples, a modified latex agglutination test was used. The highest percentage of IgG was found in sheep (87.8%) followed by cattle (86.96%) and goats (83.3%). However, the highest percentage of IgM was found in goats (16.7%) followed by cattle (13.04%) and sheep (12.2%). A trial for preparing ELISA test manually was conducted in the laboratory of the Microbiology Branch/ College of Veterinary Medicine, University of Mosul, through the isolation of the parasite (antigen) from aborted sheep fetuses. The positive latex agglutination test, were confirmed by ELISA. Of these serum samples, (93.33%) were positive.